From responsibility to accountability: Working creatively with distributed agency in office energy metering and management. (November 2015) - Whittle, R.; Ellis, R.; Marshall, I.; Alcock, P.; Hutchison, D.; Mauthe, A.
Abstract: In homes and offices across the UK, increasingly sophisticated smart metering systems are being hailed as a crucial weapon in the fight against climate change through a focus on energy demand reduction. Using the example of Current, a multi-disciplinary project focused on energy use in large office environments, this paper reflects upon the metering process on a university campus and the challenges and opportunities that it poses for energy management. Through an exploration of the relationships between the human and non-human actors that are involved in energy consumption and metering (staff, students, radiators, data loggers, thermostats, computers and building insulation, to name but a few examples), we show that, rather than being used to critique and apportion blame for energy consumption, measurement systems which attempt to quantify that consumption can provide the opportunity to ask fresh questions about agency, responsibility and the relationships between people and things in ways that can help us work towards creative solutions for more sustainable futures.